THE IMPLEMENTATION OF ELECTRONIC MEDICAL RECORD RELATED TO NURSING WORKLOAD IN INTENSIVE CARE UNIT (A LITERATURE REVIEW) - Gatra Satria; Sigit Mulyono (Journal of Innovation Research and Knowledge, 2022)
The implementation of electronic medical record has been assessed lately to review its effectiveness in reducing nursing workload. Although many studies showed its efficacy, many healthcare providers especially in Intensive Care Unit (ICU) have not implemented it yet. Studies showed that the mental and physical workload of nurses working in ICU was relatively high. It is important to find the best practice in reducing the workload. This literature review study aims to describe the implementation of electronic medical records in the intensive care unit related to nursing workload in ICU. This study used a literature review method. The databases used was ProQuest and ScienceDirect with three fundamental keywords: electronic medical record, nursing workload, and intensive care unit. Year range filter was activated to only gather journals database from 2020 to 2021. The implementation of electronic medical record can improve the service quality. However, the changing from paper-based to electronic-based medical record should be assessed carefully so it will not be a new burden to nurses